Повышение несущей способности деталей машин алмазным выглаживанием - Яценко В. К. Виктор Кузьмич; Зайцев Г. З. Григорий Зиновьевич; Притченко В. Ф. Владимир Федорович; Ивщенко Л. И. Леонид Иосифович (Москва, Машиностроение, 1985)
Авт. указаны на обороте тит. л.